PENGARUH EFEKTIVITAS FINGER PRINT TERHADAP DISIPLIN PEGAWAI PADA DINAS PEMUDA DAN OLAHRAGA (DISPORA) PROVINSI SUMATERA SELATAN - Sunarto, Sunarto; Iasha, Citra (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
The effectiveness of finger print absences is the level effectiveness of finger print absences in assessing the level of employee discipline. However, in fact the use of finger print attendance is not optimal in increasing employee discipline because there are still employees who are late in filling out attendance and go home before the appointed time and there are still employees who leave the room without the supervisor’s permission and return at a relatively short time. The pupose of this research was to examine the effect of the effectiveness of finger print attendance on employee discipline at the Department of Youth and Sports (DISPORA) of South Sumatera Province. This study used  quantitative data analysis techniques with a sample of 67 people using a saturated sample. The interpretation of the research result was adjusted to the guidelines on the relevant theory. The result of this study can be concluded that the effectiveness of finger print  attendance has a significant effect on employee discipline at the Departement of Youth and Sports of South Sumatera Province.The result of this study indicate that the effectiveness of finger print attendance on employee discipline is 61,6% and the remaining 38,4% is influenced by other factors. The result of the regression equation in this study are Y=14.236 +0.616X. The result of hypothesis tes (t count > t table) then the results of the t test in this study amounted to (6.834 > 1.997) for  the finger print absence effectiveness variable which was significant 0.00. So it can be concluded that Ho is rejected and Ha is accepted. Test result the coeficient of determination is 41,8%. The results of this study are expected to be a material consideration for the Departement of Youth and Sports (DISPORA) who wish to improve employee discipline.